Pyranopyrazolotacrines as nonneurotoxic, Aβ-anti-aggregating and neuroprotective agents for Alzheimer's disease. (June 2015) - Chioua, Mourad; Pérez-Peña, Javier; García-Font, Nuria; Moraleda, Ignacio; Iriepa, Isabel; Soriano, Elena; Marco-Contelles, José; Oset-Gasque, María Jesús
Aim: Due to the complex nature of Alzheimer's disease, there is a renewed search for multipotent, nonhepatotoxic tacrines.Results: This paper describes the synthesis and in vitro biological evaluation of eight new racemic 3-methyl-4-aryl-2, 4, 6, 7, 8, 9-hexahydropyrazolo[4′, 3′:5, 6]pyrano[2, 3- b ]quinolin-5-amines (pyranopyrazolotacrines, PPT) as nonhepatotoxic multipotent tacrine analogs. Among these compounds, PPT4 is the less hepatotoxic in the cell viability assay on HepG2 cells, showing a good neuroprotective effect in the decreased cortical neuron viability induced by oligomycin A/rotenone analysis. PPT4 is a selective and good, noncompetitive Ee AChE inhibitor, able to completely inhibit the Aβ1–40 aggregation induced by acetylcholinesterase.Conclusion: A new family of nonhepatotoxic showing selective acetylcholinesterase inhibition, permeable tacrine analogs have been discovered for the potential treatment of Alzheimer's disease.